Water Distribution Networks Optimization: a real case study. Issue 2 (2020) - Zanoli, S.M.; Astolfi, G.; Orlietti, L.; Frisinghelli, M.; Pepe, C.
Abstract: This paper presents a project aimed at the optimization of a water distribution network located in Trento (Italy). Several in-depth hydraulic studies have been conducted in order to perform hardware modifications through sectorization procedures. Advanced Process Control methods have been designed in order to optimally and automatically manage the net pressure and the scheduling of the involved pumping stations. Net pressure has been minimized through two-layer Model Predictive Control techniques, while advanced logics have been designed for the pumps scheduling. The developed Advanced Process Control system has been successfully installed on the considered network and the achieved results are here illustrated.